Factors Associated With Intentions to Engage in Vaginal Intercourse Among Sexually Abstinent Missouri High School Freshmen. (12th September 2016) - Watts, Timothy; Wilson, Kelly L.; McNeill, Elisa B.; Rosen, Brittany L.; Moore, Nancy Daley; Smith, Matthew L.
ABSTRACT: BACKGROUND: We examine personal characteristics, alcohol consumption, normative beliefs, household factors, and extracurricular engagement associated with intentions to have intercourse before marriage among abstinent students. METHODS: Data were analyzed from 245 freshmen enrolled in a school‐based abstinence‐only‐until‐marriage program. Two binary logistic regression analyses identified factors associated with intentions to engage in intercourse before marriage and within the next year. RESULTS: Approximately 21% and 14% of participants reported intentions to have intercourse. Respondents participated in 2.2 (standard deviation [SD] = 1.2) extracurricular activities. Freshmen who were male, perceived their friends to approve of premarital sex, and consumed alcohol were more likely to report intentions to have intercourse. For every additional extracurricular activity in which freshmen participated, they were less likely to report intentions to have intercourse within the next year (odds ratio [OR] = 0.56). CONCLUSIONS: Factors such as extracurricular activities provide youth with opportunities to build supportive relationships, connect with peers and role models, and positively engage in schools and communities. Extracurricular activities typically already exist, have funding, and are generally well‐supported. School‐based strategies can increase teenagers' autonomy by providing a variety of activities to participate in and reduce unsupervised time. This, in turn, has the potential to decrease sexual risk taking behaviors.